1987
DOI: 10.1007/bf02714429
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical effects of tetraethylammonium and K+ on histamine-induced contraction in pig isolated tracheal smooth muscle

Abstract: The effect of tetraethylammonium (TEA) and K+ on contractions to histamine and acetylcholine have been compared in the pig isolated trachea using organ bath and sucrose-gap techniques. Histamine elicited weak contractions, compared with acetylcholine; however, these contractions were markedly potentiated by pretreatment with TEA (10 mM) or by raising the external KCl concentration to 30-50 mM. Neither TEA nor K+ increased the sustained depolarization evoked by histamine (or acetylcholine) although oscillatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Blockade of spontaneous contractions and of K + depolarizing responses by verapamil, a blocker of voltage-operated Ca channels, indicated that current carried by Ca 2+ was likely to be involved in these responses. In short, the smooth muscle of the bronchial tree showed similar characteristics to that seen in the postnatal pig [15,16]. Moreover, strong narrowing responses to EFS were seen, which were blocked by atropine, indicating that a functional cholinergic nervous supply was present.…”
Section: Discussionmentioning
confidence: 51%
“…Blockade of spontaneous contractions and of K + depolarizing responses by verapamil, a blocker of voltage-operated Ca channels, indicated that current carried by Ca 2+ was likely to be involved in these responses. In short, the smooth muscle of the bronchial tree showed similar characteristics to that seen in the postnatal pig [15,16]. Moreover, strong narrowing responses to EFS were seen, which were blocked by atropine, indicating that a functional cholinergic nervous supply was present.…”
Section: Discussionmentioning
confidence: 51%
“…Together, our data suggest that Ca 2ϩ influx through the reverse mode of the NCX contributes substantially to increasing the pool of intracellular Ca 2ϩ necessary for refilling of the SR. Since the removal of extracellular Na ϩ and KB-R7943 had no effect on contractions mediated by KCl [involving L-type Ca 2ϩ channels (22,23,26,31,39) and RhoA/ROCK signaling (9,18,25,30,36)] but significantly reduced agonist-induced contractions (involving those same pathways as well as release of the internal Ca 2ϩ pool), we conclude that the reductions observed during our interventions were due to specific targeting of the reverse mode of the NCX and subsequent refilling of the internal Ca 2ϩ pool. Thus the data are consistent with our hypothesis that Ca 2ϩ influx via the reverse mode of the NCX is essential to the refilling of the SR following Ca 2ϩ mobilization by a variety of physiological agonists.…”
Section: Discussionmentioning
confidence: 99%
“…KCl is widely used to trigger voltage-dependent Ca 2ϩ -influx (22,23,26,31,39) and has also recently been shown to stimulate the RhoA/ROCK signaling pathway (9,18,25,30,36), but it does not evoke Ca 2ϩ release in ASM. To determine whether our interventions targeting the NCX activity had any effect on those signaling events outside of Ca 2ϩ release, we examined contractions triggered by KCl (60 mM).…”
Section: Effect Of Inhibition Of the Ncx On Successive 5-ht-induced Cmentioning
confidence: 99%
“…-activated K + (Kca) channel blockers charybdotoxin and iberiotoxin [15][16][17][18]. On the other hand, the oscillatory contractions can be inhibited by the removal of external Ca 2+ and by addition of Ca 2+ channel blockers [15,16,18] or a protein kinase C (PKC) inhibitor, but are enhanced by a PKC activator [18].…”
Section: +mentioning
confidence: 99%